Quantificação de poluentes emitidos durante a queima de biomassa florestal em laboratório - Amaral, Simone Simões [UNESP] (2014)
Various pollutants are released into the atmosphere through the burning of forest biomass. Identify and quantify emissions of these compounds is of fundamental importance to the understanding of its effects. Thus, this work aims to quantify the main pollutants emitted during the burning of the forest biomass of the Amazon and Araucaria. Gas concentrations (CO2, CO, NOx) and particulate matter smaller than 2.5 μm (PM2.5) were quantified. The behavior of temperature, burning rate, modified combustion efficiency (MCE) and emission factor (EF) along the burning of biomass also were evaluated. Concentration and diameter values of particulate matter were discussed regarding the stages of combustion (flame and smoldering). The biomasses were characterized chemically, in order to evaluate possible relationships between their composition and the emission of pollutants. Approximately 2 kg each biomass was burned, whose moisture content was around 12 %. PM2.5 sampling was made using two equipment (DataRam4 and Cascade Impactor), already in gaseous sampling was used a continuous analyzer specific (Rosemount Analytical). The biomass of Araucaria showed the higher lignin content (35%) and higher CO2 emission factor (1,708.30 ± 127.91 g/kg), when compared to the biomass of the Amazon, whose CO2 EF was 1,581 ± 28.88 g/kg. Higher EF CO was obtained on burning in the Amazon biomass (48.61 ± 6.74 g/kg). The CO2 emission factor and CO appeared to be influenced by the lignin content of biomass. The biomass of Araucaria issued higher particles and in higher concentrations when compared to the biomass of the Amazon. Positive correlations were observed between the EF PM2.5 and CO2 with the ECM